Erbium Yttrium–Aluminum–Garnet Laser Versus Traditional Bur in the Extraction of Impacted Mandibular Third Molars: Analysis of Intra- and Postoperative Differences. Issue 8 (November 2018) - Giovannacci, Ilaria; Giunta, Giovanna; Pedrazzi, Giuseppe; Meleti, Marco; Manfredi, Maddalena; Migliario, Mario; Brucoli, Matteo; Greco Lucchina, Alberta; Mortellaro, Carmen; Vescovi, Paolo
Abstract : Introduction: Different osteotomy techniques have been proposed in order to improve postoperative course of impacted third molar extraction. The aim is to evaluate the possible advantages achieved with erbium yttrium–aluminum–garnet (Er:YAG) laser osteotomy compared with traditional burs. Materials and Methods: Seventy-six extractions were randomly classified into 2 groups according to osteotomy instrument: group 1 (G1)—Er:YAG laser: 35 patients; group 2 (G2)—traditional bur: 41 patients. Intraoperative parameters: total time, stitches number, and patient compliance. Postoperative: pain, health-related quality of life (HR-QoL), need for analgesics, edema, trismus, intra- and extraoral hematoma, and postoperative complications. Results: Mean time for G1 resulted 1069.4 seconds; for G2 1913.5 seconds ( P < 0.0001). Mean number of stitches ( P = 0.773) and patient compliance ( P = 0.063) were not statistically different. Regarding pain, mean visual analog scale (VAS), and numeric rating scale (NRS) scores were lower in G1 than in G2. Statistically significant differences were highlighted at days 0, 1, and 3 with VAS scale and at days 0, 1, 3, and 7 with NRS scale. The HR-QoL scores resulted lower in G1 than in G2 ( P < 0.0001). Mean facial swelling and trismus resulted statistically lower in G1 than in G2 at day 2 ( P < 0.0001). Trismus resulted statistically lower in G1 than in G2 at days 2 ( P < 0.0001) and 7 ( P = 0.004). Two patients (5.71%) of subcutaneous emphysema was recorded in G1 and 2 patients (4.88%) of lip paresthesia in G2. Conclusion: Data confirm that the use of Er:YAG laser for osteotomy may achieve several advantages both technical and biological.